Analisis Efisiensi Kerja Kompressor Pada Mesin Refrigerasi di PT. XYZ - Ahmad Jibril; Cakranegara, Pandu Adi; Putri, Raudya Setya Wismoko; Octiva, Cut Susan (Jurnal Mesin Nusantara, 2022)
Refrigeration is one way to maintain the temperature of a material or a room at a lower level than the ambient temperature conditions around it by absorbing heat from the material or room. The refrigeration system that is widely used today for industrial purposes is to use a vapor compression cycle, where in this vapor compression cycle one of the components that has an important role is the compressor. Over time, the performance of the compressor will decrease, so it will affect the heat absorption process of the material to be cooled. With the reduced ability of the heat absorption process, it will reduce the efficiency level of the compressor. Based on the results of the efficiency analysis on the performance of the refrigeration system compressor at PT. XYZ, then the efficiency value is 73.98%.